Semi (1, 2)*-Maximal Soft (1, 2)*-Pre-Open Sets and Semi (1, 2)*-Minimal Soft (1, 2)*-Pre-Closed Sets In Soft Bitopological Spaces - Mahmood , Sabiha I. (Iraqi Journal of Science, 2022)
In this paper, we introduce and study new types of soft open sets and soft closedsets in soft bitopological spaces (X,~ ,~ ,E) 1 2   , namely, (1,2)*-maximal soft opensets, (1,2)*-maximal soft (1,2)*-pre-open sets, semi (1,2)*-maximal soft (1,2)*-preopensets, (1,2)*-maximal soft closed sets, (1,2)*-maximal soft (1,2)*-pre-closedsets, (1,2)*-minimal soft open sets, (1,2)*-minimal soft (1,2)*-pre-open sets, (1,2)*-minimal soft closed sets, (1,2)*-minimal soft (1,2)*-pre-closed sets, and semi (1,2)*-minimal soft (1,2)*-pre-closed sets. Also, properties and the relation among theseconcepts have been studied.